Agenesis of the corpus callosum with Probst bundles owing to haploinsufficiency for a gene in an 8 cM region of 6q25. Issue 12 (December 1998) - Pirola, B; Bortotto, L; Giglio, S; Piovan, E; Janes, A; Guerrini, R; Zuffardi, O
Abstract : Agenesis of the corpus callosum (ACC) is a relatively common brain abnormality resulting from developmental defects either limited to the structures leading to the proper formation of the corpus callosum or involving the embryo forebrain more generally. ACC is genetically heterogeneous with autosomal dominant, autosomal recessive, and X linked inheritance and has also been reported in subjects with aneuploidies involving several chromosomes. Among them, distal 6q deletions have been consistently reported in association with ACC, suggesting that there is a gene in the deleted region whose haploinsufficiency impairs normal corpus callosum development. We have studied a child with ACC with Probst bundles and a deletion at 6q25 of about 8 cM, from D6S1496 to D6S437. Probst bundles are the axons that should have formed the corpus callosum but, unable to cross the midline owing to absence of the massa commissuralis, they run longitudinally along the medial walls of the lateral ventricles from the frontal to the occipital lobes. Thus, their presence suggests that a gene located in the 6q deleted region is specifically involved in the formation of the massa commissuralis and that its haploinsufficiency leads to primary ACC.